IHML: Incremental Heuristic Meta-Learner - Onur Karadeli; Kıymet Kaya; Şule Gündüz Öğüdücü (Applied Artificial Intelligence)
The landscape of machine learning constantly demands innovative approaches to enhance algorithms’ performance across diverse tasks. Meta-learning, known as “learning to learn” is a promising way to overcome these diversity challenges by blending multiple algorithms. This study introduces the IHML: Incremental Heuristic Meta-Learner, a novel meta-learning algorithm for classification tasks. By leveraging a variety of base-learners with distinct learning dynamics, such as Gaussian, tree, and instance, IHML offers a comprehensive solution adaptable to different data characteristics. Moreover, the core contributions of IHML lie in its ability to tackle the optimal base-learner and feature sets determination mechanism with the help of Explainable Artificial Intelligence (XAI) and heuristic elbow methods. Existing work in this context utilizes XAI mostly in pre-processing the data or post-analysis of the results, however, IHML incorporates XAI into the learning process in an iterative manner and improves the prediction performance of the meta-learner. To observe the performance of the proposed IHML, we used five different datasets from astrophysics, physics, biology, e-commerce, and economics. The results show that the proposed model achieves more accuracy (in average % 10 and at most % 71 improvements) compared to the baseline machine learning models in the literature.